2017
DOI: 10.3122/jabfm.2017.04.170039
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Transforming Established Primary Care Practices to Patient-Centered Medical Homes (PCMHs)

Abstract: Background:The patient-centered medical home (PCMH) shows promise for improving care and reducing costs. We sought to reduce the uncertainty regarding the time and cost of PCMH transformation by quantifying the direct costs of transforming 57 practices in a medical group to National Committee for Quality Assurance (NCQA)-recognized Level III PCMHs.Methods: We conducted structured interviews with corporate leaders, and with physicians, practice administrators, and office managers from a representative sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…In this section, we review the methods used by eight studies that attempted to measure costs that practices incurred in delivering comprehensive primary care capabilities (Zuckerman et al, 2009;Nocon et al, 2012;Patel et al, 2013;Magill et al, 2015;Halladay et al, 2016;Martsolf et al, 2016;Shao et al, 2016;Fleming et al, 2017). To identify these eight studies, we used a directed reference mining approach.…”
Section: Overview Of Past Approaches To Cost Estimation For Comprehenmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we review the methods used by eight studies that attempted to measure costs that practices incurred in delivering comprehensive primary care capabilities (Zuckerman et al, 2009;Nocon et al, 2012;Patel et al, 2013;Magill et al, 2015;Halladay et al, 2016;Martsolf et al, 2016;Shao et al, 2016;Fleming et al, 2017). To identify these eight studies, we used a directed reference mining approach.…”
Section: Overview Of Past Approaches To Cost Estimation For Comprehenmentioning
confidence: 99%
“…The eight studies focused on the costs that practices incurred either by (1) becoming a PCMH and/or applying for PCMH recognition or (2) developing and maintaining comprehensive capabilities within the context of PCMH. Two studies estimated the costs of applying for National Committee for Quality Assurance (NCQA) Level 3 medical home recognition (Halladay et al, 2016;Fleming et al, 2017). The remaining studies focused on estimating the costs of developing and maintaining capabilities consistent with the PCMH model (Magill et al, 2015;Martsolf et al, 2016).…”
Section: How Studies Defined "Comprehensive Primary Care"mentioning
confidence: 99%
See 1 more Smart Citation
“…Fleming et al 7 found substantial costs for individual practices to attain or renew National Committee for Quality Assurance Level III recognition, even when those practices are supported centrally through a large medical group's corporation and with a common electronic health record. The total incremental cost for initial recognition between the corporation and individual practice was estimated at around $43,000 per 5-physician practice.…”
Section: Health Services and Practice Methodsmentioning
confidence: 99%
“…The most widely used recognition for what constitutes a PCMH is the process established by the National Committee for Quality Assurance (NCQA). [8][9][10][11] Minnesota was one of the first states to implement its own vol-untary certification process for primary care practices in 2010, based on demonstration that a practice met 5 standards (criteria) after thorough review 12 : (1) continuous access and communications with patients and family; (2) an electronically searchable registry to identify care gaps and manage services; (3) care coordination for patient-and family-centered care; (4) care plans that involve patients with chronic or complex conditions; and (5) continuous improvement in patient satisfaction, outcomes, and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%